BLOOD PRESSURE PATTERN AMONG COMPUTER AND MOBILE PHONE USERS IN POPULATION AGED 13 YEARS AND ABOVE IN URBAN KANPUR - Tandon, Richa; Srivastava, J P; Saxena, S C; Srivastava, V K; Nigam, Seema (Indian Journal of Community Health, 2007)
.